Synthesis, growth inhibitory activity on human tumor cell lines and evaluation of the hepatotoxicity of di(hetero)arylethers and di(hetero)arylamines in the thieno[3,2-b]pyridine series - Calhelha, Ricardo C. (2013)
Acknowledgments: To the Foundation for the Science and Technology (FCT–Portugal) for financial support through the NMR Portuguese network (Bruker 400 Avance III-Univ Minho). To FCT and FEDER-COMPETE/QREN/EU for financial support through the research unities PEst-C/QUI/UI686/2011 and PEst-OE/AGR/UI0690/2011, the research project PTDC/QUI-QUI/111060/2009 and the post-Doctoral grant attributed to R.C.C. (SFRH/BPD/68344/2010) also financed by POPH and FSE.